Dynamic evolution of telomeric sequences in the green algal order Chlamydomonadales - Fulnečková, Jana; Hasíková, Tereza; Fajkus, Jiří; Lukešová, Alena; Eliáš, Marek; Sýkorová, Eva (Genome biology and evolution, 2012)
Telomeres, which form the protective ends of eukaryotic chromosomes, are a ubiquitous and conserved structure of eukaryotic genomes but the basic structural unit of most telomeres, a repeated minisatellite motif with the general consensus sequence T(n)A(m)G(o), may vary between eukaryotic groups. Previous studies on several species of green algae revealed that this group exhibits at least two types of telomeric sequences, a presumably ancestral type shared with land plants (Arabidopsis type, TTTAGGG) and conserved in, for example, Ostreococcus and Chlorella species, and a novel type (Chlamydomonas type, TTTTAGGG) identified in Chlamydomonas reinhardtii. We have employed several methodical approaches to survey the diversity of telomeric sequences in a phylogenetically wide array of green algal species, focusing on the order Chlamydomonadales. Our results support the view that the Arabidopsis-type telomeric sequence is ancestral for green algae and has been conserved in most lineages, including Mamiellophyceae, Chlorodendrophyceae, Trebouxiophyceae, Sphaeropleales, and most Chlamydomonadales. However, within the Chlamydomonadales, at least two independent evolutionary changes to the Chlamydomonas type occurred, specifically in a subgroup of the Reinhardtinia clade (including C. reinhardtii and Volvox carteri) and in the Chloromonadinia clade. Furthermore, a complex structure of telomeric repeats, including a mix of the ancestral Arabidopsis-type motifs and derived motifs identical to the human-type telomeric repeats (TTAGGG), was found in the chlamydomonadalean clades Dunaliellinia and Stephanosphaeria. Our results indicate that telomere evolution in green algae, particularly in the order Chlamydomonadales, is far more dynamic and complex than thought before. General implications of our findings for the mode of telomere evolution are discussed.
Keywords: Chlorophyta; molekulární evoluce; Evolution, Molecular; telomery; Telomere; Volvocida